TNFα-Damaged-HUVECs Microparticles Modify Endothelial Progenitor Cell Functional Activity - Luna, Carlos; Carmona, Andrés; Alique, Matilde; Carracedo, Julia; Ramirez, Rafael (Frontiers in Physiology, 2015)
Endothelial progenitor cells (EPCs) have an important role in the maintenance of vascular integrity and homeostasis. While there are many studies that explain EPCs mechanisms action, there are few studies that demonstrate how they interact with other emerging physiological elements such as Endothelial Microparticles (EMPs). EMPs are membranous structures with a size between 100-1000nm that act as molecular information transporter in biological systems and are known as an important elements in develop of different pathologies; moreover a lot of works explains that are novel biomarkers. To elucidate these interactions, we proposed an in vitro model of endothelial damage mediated by TNF-alpha, in which damaged EMPs and EPCs are in contact to assess EPCs functional effects. We have observed that damaged EMPs can modulate several EPCs classic factors as colony forming units (CFUs), contribution to repair a physically damaged endothelium (wound healing), binding to mature endothelium, and co-adjuvants to the formation of new vessels in vitro (angiogenesis). All of these in a dose-dependent manner. Damaged EMPs at a concentration of 103 MPs/ml have an activating effect of these capabilities, while at concentrations of 105 MPs/ml these effects are attenuated or reduced. This in vitro model helps explain that in diseases where there is an imbalance between these two elements (EPCs and damaged EMPs), the key cellular elements in the regeneration and maintenance of vascular homeostasis (EPCs) are not fully functional, and could explain, at least in part, endothelial dysfunction associated in various pathologies.